2019
DOI: 10.1002/mds.27870
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in Parkinson's disease: A transcranial magnetic stimulation study

Abstract: Background Demographic and clinical studies imply that female sex may be protective for PD, but pathophysiological evidence to support these observations is missing. In early PD, functional changes may be detected in primary motor cortex using transcranial magnetic stimulation. Objective We hypothesised that if pathophysiology differs between sexes in PD, this will be reflected in differences of motor cortex measurements. Methods Forty‐one newly diagnosed PD patients (22 males, 19 females) were clinically asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 85 publications
1
16
0
Order By: Relevance
“…Indeed, the abnormal excitability of intracortical circuits have been found in subjects with PD (even if not in all reports) with evidence of reduced intracortical inhibition and increased intracortical facilitation (Ni et al 2013;Shirota et al 2019). Other abnormalities of cortical excitability in PD concerning gender (Kolmancic et al 2019) and asymmetry of motor involvement have also been reported, particularly in early PD patients, with an interhemispheric imbalance of excitability, and abnormal transcallosal inhibition (Spagnolo et al 2013).…”
Section: Introductionmentioning
confidence: 94%
“…Indeed, the abnormal excitability of intracortical circuits have been found in subjects with PD (even if not in all reports) with evidence of reduced intracortical inhibition and increased intracortical facilitation (Ni et al 2013;Shirota et al 2019). Other abnormalities of cortical excitability in PD concerning gender (Kolmancic et al 2019) and asymmetry of motor involvement have also been reported, particularly in early PD patients, with an interhemispheric imbalance of excitability, and abnormal transcallosal inhibition (Spagnolo et al 2013).…”
Section: Introductionmentioning
confidence: 94%
“…It has been established that women are more likely than men to experience sleep disturbances especially after menopause, with 35% to 60% of postmenopausal women reporting significant sleep disturbance (18). Sex differences in PD have also been established whereby higher prevalence and earlier age at onset are frequently observed in men (19)(20)(21)(22)(23)(24)(25). Furthermore, limited evidence has suggested that women with PD experience more sleep disturbances than men, although biological mechanisms for these sex differences are less well understood (7).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that patients with PD have a wide range of disorders of neurophysiological parameters in the primary motor cortex, which are correlated in direct proportion to the severity of clinical motor symptoms of PD [2,8]. Neurophysiological parameters of the central nervous system (CNS) can be assessed using transcranial magnetic stimulation (TMS) [4,10].…”
mentioning
confidence: 99%
“…Neurophysiological parameters of the central nervous system (CNS) can be assessed using transcranial magnetic stimulation (TMS) [4,10]. The method of diagnostic TMS makes it possible to assess the excitability of the nervous system using the parameters of motor evoked potential (MEP), which include latency, amplitude and duration [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation